Semantic Interpretation of Tubuh yang Padam Tersulut Lyrics by Harum Manis: Interpretasi Semantik pada Lirik Lagu Tubuh Yang Padam Tersulut Karya Harum Manis - Ariella, Angela Gysca (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
Music and song lyrics serve as universal communication media. Semantic interpretation in song lyrics is intriguing to study due to their often ambiguous language. Words in song lyrics may have literal, metaphorical, or symbolic meanings, depending on context and delivery. This study explores the semantic richness in Harum Manis's Tubuh yang Padam Tersulut, focusing on how its lyrics convey emotions of loss through evocative language. Using qualitative descriptive analysis, this research identifies layers of meaning, including literal and figurative interpretations, highlighting the contextual importance in understanding lyrics. The findings reveal a profound emotional journey, intertwining fond memories and the pain of separation. This study underscores the significance of contextual understanding in interpreting lyrics and offers recommendations for further analyses in literature and music studies.